2020
DOI: 10.1002/anie.202010090
|View full text |Cite
|
Sign up to set email alerts
|

Expeditious Total Synthesis of Hemiasterlin through a Convergent Multicomponent Strategy and Its Use in Targeted Cancer Therapeutics

Abstract: Hemiasterlin is an antimitotic marine natural product with reported sub-nanomolar potency against several cancer cell lines. Herein, we describe an expeditious total synthesis of hemiasterlin featuring a four-component Ugi reaction (Ugi-4CR) as the key step. The convergent synthetic strategy enabled rapid access to taltobulin (HTI-286), a similarly potent synthetic analogue. This short synthetic sequence enabled investigation of both hemiasterlin and taltobulin as cytotoxic payloads in antibody-drug conjugates… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 51 publications
0
13
0
Order By: Relevance
“…X-ray crystallography analysis of 15 a was used to determine its absolute stereochemistry, which corresponded to the stereochemistry of hemiasterlin (Scheme 3 b). [50] The low diastereoselectivity observed in the Ugi-4CR step was similarly experienced in many previous total syntheses which utilised isocyanide-based multicomponent reactions (IMCRs), [32][33][34][35][36] where notable exceptions were when cyclic imines were used. [37,38] Consequently, several groups have reported the use of chiral phosphoric acids (CPAs) to induce enantioselectivity for IMCRs.…”
mentioning
confidence: 70%
See 2 more Smart Citations
“…X-ray crystallography analysis of 15 a was used to determine its absolute stereochemistry, which corresponded to the stereochemistry of hemiasterlin (Scheme 3 b). [50] The low diastereoselectivity observed in the Ugi-4CR step was similarly experienced in many previous total syntheses which utilised isocyanide-based multicomponent reactions (IMCRs), [32][33][34][35][36] where notable exceptions were when cyclic imines were used. [37,38] Consequently, several groups have reported the use of chiral phosphoric acids (CPAs) to induce enantioselectivity for IMCRs.…”
mentioning
confidence: 70%
“…[25] A separable mixture of diastereomers 9 a and 9 b were obtained in good yield (70 %, dr 1:1.3), of which we identified the absolute stereochemistry by X-ray crystallography analysis. [50] Trifluoroacetic acid was used as the resulting N-trifluoroacetamide is stable under mild ester hydrolysis condition and can also be removed orthogonally using reductive methods. [29,30] It was found that the use of 3 molecular sieves were critical to reaction progression; alternative drying reagents resulted in the formation of undesired side products (Scheme S1).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…3). As with previous IgG conjugations employing the DVP motif 15,23,26,27 , the four interchain disulfides of trastuzumab were first reduced by treatment with tris(2-carboxyethyl)phosphine (TCEP). Upon subsequent addition of 2 or 8, the reduced disulfides were rebridged via the bis-reactive DVP, affording conjugates ADC 1 and ADC 2 with four drugs/antibody.…”
Section: A Novel Enzyme Cleavable Linker For Antibody-drug Conjugatesmentioning
confidence: 99%
“…We have previously reported divinylpyrimidine and divinyltriazine reagents for cysteine cross-linking. [40][41][42][43][44][45][46][47] While stable and functional modication of proteins or peptides could be achieved with these reagents, they are only useful when two proximal cysteine residues are present in the protein of interest. To expand the scope and generality of this scaffold, it was envisioned that monovinylheteroarene reagents would enable efficient and selective modication of single cysteine residues, regardless of spatial arrangement.…”
Section: Introductionmentioning
confidence: 99%